Climate-resilient aquatic food systems require transformative change to address gender and intersectional inequalities - Adam, Rahma; Amani, Anamika; Kuijpers, Rob; Danielsen, Katrine; Smits, Esther; Kruijssen, Froukje; Moran, Nicole; Tigchelaar, Michelle; Wabnitz, Colette; Tilley, Alexander; Luzzi, Matteo; Hossain, Peerzadi; et al. (Public Library of Science, 2024)
The adverse impacts of climate change on aquatic food systems (AFS) and the people who depend on AFS for livelihood security are inequitably distributed between and within countries. People facing the highest risks and experiencing the severest impacts of climate change are those who already experience multidimensional inequalities in their lives, particularly because of their gender, class, age, indigeneity, ethnicity, caste, religion, and the physical and political conditions that can create additional vulnerabilities. In this paper, we conducted a scoping review of the literature that explores the links between climate change, gender, and other social identities, and AFS. The review was complemented by an analysis of representative data on women and men aquaculture farmers in Bangladesh from 2018 to 2019. We also analysed data from the 2019 Illuminating Hidden Harvest project. The study relied on the gendered agrifood system and aquatic food climate risk frameworks to guide on literature search, review, and data analyses. Our findings show that intersecting identities disadvantage certain AFS actors, particularly young women from minority ethnic groups, and create challenge for them to manage and adapt to climate shocks and stresses. Examples of gender-responsive and transformative interventions are highlighted from our review to showcase how such intersectional disadvantages can be addressed to increase women’s empowerment and social and gender equality.